Development of Biotechnology E-Module Based on Project-Based ‎Learning Integrated with Betawi Local Wisdom to Enhance ‎Creative Thinking Skills - Arsita Oktaviani; Endang Susantini; Mahanani Tri Asri (Yayasan Darussalam Bengkulu, 2026)
Improving the quality of education as part of achieving Sustainable Development Goal (SDG) 4: Quality Education requires the development of innovative teaching materials that can facilitate 21st-century skills, including creative thinking abilities. This study aims to develop and validate biotechnology e-module based on Project-Based Learning (PjBL) that integrates Betawi local wisdom and focuses on students’ creative thinking skills. This study employed a Research and Development (R&D) approach using the 4D model adapted from Thiagarajan. The resulting product is a biotechnology e-module based on PjBL integrated with Betawi local wisdom and oriented toward creative thinking skills. This study involved 69 eleventh-grade students and 2 teachers at SMAN 98 Jakarta. The instruments used included an expert validation sheet, a teacher observation sheet, and a student response questionnaire. E-module was validated by experts in content, language, and design. The validation results indicated that the media was very feasible, with a scores of 90,8% for content, 94,4% for design and 91,6% for language. The results of e-module’s practicality showed an average percentage of 91,36% from students and 91.56% from teachers, with the category very practical. These findings indicate that the developed e-module is valid and practical for use in learning and supports the development of creative thinking skills.